2010
DOI: 10.3354/meps08302
|View full text |Cite
|
Sign up to set email alerts
|

Territorial damselfishes facilitate survival of corals by providing an associational defense against predators

Abstract: Territorial defense by the herbivorous damselfishes, Stegastes nigricans and S. lividus, benefits the hermatypic corals growing inside their territories. Coral diversity was significantly higher inside damselfish territories at 2 sites in Moorea, French Polynesia, and at 1 site in Guam, Mariana Islands. In Guam, this pattern was stable for at least 10 yr. Certain coral species, including Pocillopora damicornis, were found only inside damselfish territories at these sites. All fishes, including coral-feeding bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
65
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 56 publications
2
65
1
Order By: Relevance
“…However, the present study and other recent findings (e.g Pratchett 2007, Gochfeld 2010 have all demonstrated that polyp feeding corallivores are a highly selective functional group that consumes considerably more coral tissue than previously suspected. They are capable of having significant effects upon the structure of the coral community, especially after major disturbance events (Bellwood et al 2006, Gochfeld 2010. The energetic cost imposed by coral-feeders upon coral colonies still needs to be quantified and incorporated into coral reef resilience models, as it is likely that this chronic stress will interact with and be potentially compounded by future anthropogenic stresses.…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations
“…However, the present study and other recent findings (e.g Pratchett 2007, Gochfeld 2010 have all demonstrated that polyp feeding corallivores are a highly selective functional group that consumes considerably more coral tissue than previously suspected. They are capable of having significant effects upon the structure of the coral community, especially after major disturbance events (Bellwood et al 2006, Gochfeld 2010. The energetic cost imposed by coral-feeders upon coral colonies still needs to be quantified and incorporated into coral reef resilience models, as it is likely that this chronic stress will interact with and be potentially compounded by future anthropogenic stresses.…”
Section: Discussioncontrasting
confidence: 52%
“…Further, the intensity of predation on these very small colonies was the lowest of all size classes, which suggests predation-induced mortality by polyp-feeders on juvenile corals is only likely to occur when these small colonies are the only remaining corals left on a reef (e.g. Samways 2005, Gochfeld 2010). Likewise, very large corals are also expected to experience a lower net effect from chronic predation as the impact of tissue loss is dispersed over a larger surface area, with larger colonies having a greater capacity for regeneration (Oren et al 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While wider foraging ranges may conversely result from reliance on specific, rare resources, their robust jaw morphology (Bellwood, 1994) and a gut able to process high sediment loads (Choat et al, 2002) support the first interpretation, as they allow the fish to process more foods with differing isotopic values. In contrast, farming damselfish actively select the composition of their 1m 2 territories (Hata and Kato, 2004;Ceccarelli et al, 2005) which counterintuitively can also lead to higher diversity via intermediate disurbance (Gochfeld, 2010). Their restricted niche values suggest that they are reduced in the number of food sources that they assimilate in comparison to the parrotfish.…”
Section: Discussionmentioning
confidence: 98%